2018
DOI: 10.1158/1541-7786.mcr-17-0686
|View full text |Cite
|
Sign up to set email alerts
|

Thymidine Kinase 1 Loss Confers Trifluridine Resistance without Affecting 5-Fluorouracil Metabolism and Cytotoxicity

Abstract: Acquired resistance to therapeutic drugs is a serious problem for patients with cancer receiving systemic treatment. Experimentally, drug resistance is established in cell lines by repeated, continuous exposure to escalating concentrations of the drug; however, the precise mechanism underlying the acquired resistance is not always known. Here, it is demonstrated that the human colorectal cancer cell line DLD1 with acquired resistance to trifluridine (FTD), a key component of the novel, orally administered nucl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…S3). Furthermore, a recent study reported a similar finding in TK1 -knock-out DLD-1 cells 10 , suggesting that TK1 is essential for FTD cytotoxicity in a range of cell lines.
Figure 1FTD cytotoxicity in TK1 -knock-out cells. ( A ) Schematic diagram of the TK1 locus on Chr17q25.3.
…”
Section: Resultssupporting
confidence: 61%
“…S3). Furthermore, a recent study reported a similar finding in TK1 -knock-out DLD-1 cells 10 , suggesting that TK1 is essential for FTD cytotoxicity in a range of cell lines.
Figure 1FTD cytotoxicity in TK1 -knock-out cells. ( A ) Schematic diagram of the TK1 locus on Chr17q25.3.
…”
Section: Resultssupporting
confidence: 61%
“…HCT-116 cells were purchased from American Type Culture Collection in 2011. DLD1 cells were provided by Taiho Pharmaceutical Co. Ltd. (22). A549 cells were provided by Dr. M. Takeshita (Kyushu University) (21).…”
Section: Cell Culture and Reagentsmentioning
confidence: 99%
“…The treatment sequence is an important element of our trial 4 . We previously showed that 5‐FU‐based chemotherapy is effective even in tumors becoming refractory to FTD after trifluridine/tipiracil treatment 22 . Since FTD/TPI does not have cross‐resistance with 5‐fluorouracil, 10,13,23 capecitabine/Bev can be selected as a subsequent therapy.…”
Section: Discussionmentioning
confidence: 99%